Efek Sterilisasi dan Komposisi Media Produksi Inokulan Fungi Mikoriza Arbuskula terhadap Kolonisasi Akar, Panjang Akar dan Bobot Kering Akar Sorgum - Tarra Martiana Dewi; Anne Nurbaity; Pujawati Suryatmana; Emma Trinurani Sofyan (Jurusan Agroteknologi, 2017)
Quality of biofertilizer such as arbuscular myorrhizal fungi could be improved through the selection of appropriate sterilization and composition of the medium. The objective of the experiment was to determine the effect of sterilization and carrier composition on root colonisation, root length and weight of sorghum root. A green house experiment was conducted in randomized block design. The factors were: 1. methods of sterilization (ie. control; autoclave; NaOCl 10%; Co-60 gamma irradiation), and 2. composition of the carrier of mycorrhiza (100% zeolite; 75% zeolite + 25% rice charcoal; 50% zeolite + 50% rice charcoal). Results showed that there was no interaction effect of sterilization and composition of carrier on root colonisation, root length and weight of sorghum root. However, different technique of sterilisation gave differences on root colonisation, root length and weight of sorghum root. Sterilization using NaOCl 10% was not recommended. Gamma Co-60 irradiation sterilization did not have difference with control and autoclave, however there was tendency that irradiation technique gave better results to all parameters measured.